Association of long-term exposure to PM2.5 with hypertension prevalence and blood pressure in China: a cross-sectional study - Jing Li; Shuang Hu; Yan Gao; Di Zhang; Jiali Song; Matteo Renzi; Emanuela Medda; Guigang Tang; Wenbo Zhang; Maria Antonietta Stazi (BMJ Open)
Objective Evidence of the effects of long-term fine particulate matter (PM2.5) exposure on hypertension and blood pressure is limited for populations exposed to high levels of PM2.5. We aim to assess associations of long-term exposure to PM2.5 with hypertension prevalence and blood pressure, and further explore the subpopulation differences and effect modification by participant characteristics in these associations in China.Methods We analysed cross-sectional data from 883 827 participants aged 35–75 years in the China Patient-Centred Evaluative Assessment of Cardiac Events Million Persons Project. Data from the monitoring station were used to estimate the 1-year average concentration of PM2.5. The associations of PM2.5 exposure with hypertension prevalence and blood pressure were investigated by generalised linear models, with PM2.5 included as either linear or spline functions.Results The 1-year PM2.5 exposure of the study population ranged from 8.8 to 93.8 µg/m3 (mean 49.2 µg/m3). The adjusted OR of hypertension prevalence related to a 10 μg/m3 increase in 1-year PM2.5 exposure was 1.04 (95% CI, 1.02 to 1.05). Each 10 μg/m3 increment in PM2.5 exposure was associated with increases of 0.19 mm Hg (95% CI, 0.10 to 0.28) and 0.13 mm Hg (95% CI, 0.08 to 0.18) in systolic blood pressure and diastolic blood pressure, respectively. The concentration–response curves for hypertension prevalence and systolic blood pressure showed steeper slopes at higher PM2.5 levels; while the curve for diastolic blood pressure was U-shaped. The elderly, men, non-current smokers and obese participants were more susceptible to the exposure of PM2.5.Conclusions Long-term exposure to PM2.5 is associated with higher blood pressure and increased risk of hypertension prevalence. The effects of PM2.5 on hypertension prevalence become more pronounced at higher PM2.5 levels. These findings emphasise the need to reduce air pollution, especially in areas with severe air pollution.